Genetics of Norwegian kelp forests: Microsatellites reveal the genetic diversity, differentiation, and structure of two foundation kelp species in Norway - Evankow, Ann Marie (2015)
Various stressors such as higher temperatures, grazing by sea urchins, and anthropogenic effects may threaten kelp forests around the world. Conservation efforts can benefit from an understanding of current and historic patterns of gene flow and population connectivity of kelp. However, relatively little is known about these patterns, especially with regards to the northern edge of the distribution of kelp species in the North Atlantic Ocean. Knowledge of kelp population genetic diversity and structure can provide crucial information about the resilience and recolonization potential for already threatened populations. This study investigated the genetic diversity, differentiation, and structure of the two foundation kelp species in Norway, Saccharina latissima and Laminaria hyperborea. Nearly 500 individuals were genotyped from 16 different sites along the Norwegian coast using microsatellite loci that cross-amplified from other species. Roughly half of the samples per species amplified and were score-able for three polymorphic markers for S. latissima and 11 for L. hyperborea. Significant genetic structure, differentiation, and variation in genetic diversity were found among sites for both species. There were at least two distinct clusters of S. latissima and four of L. hyperborea. Genetic patterns corresponding to isolation by distance were significant for both species, except within the Skagerrak region. Genetic diversity of L. hyperborea was low in the Skagerrak region and significantly increased with higher latitudes along the Norwegian coast. Genetic diversity of S. latissima was significantly different between sites, but did not vary significantly between larger regions. Overall, this study established molecular tools for future investigations and provided the first glimpse into population genetic patterns of S. latissima and L. hyperborea in Norway.